Modern Fiber Art Creation Based on Traditional Hakka Hand Tie-Dyeing Process Based on Carbon Nanotube Nanomaterials - Fuying Zhang (Advances in Materials Science and Engineering)
With the change of the times, modern fiber art has greatly changed and developed in the traditional technology. This artistic expression brings people richness in form and artistic language and is a kind of performance art between art and decoration. Modern fiber art is a part of life. With the change of living environment, people's things will also change, so if we want to adapt, we have to change appropriately. Molecular dynamics and calculation of resistance values are used to study the relationship between the length, cross section, and temperature of materials in carbon nanotube composites. Modern fibers are mainly made of composite materials such as carbon nanotubes. This paper mainly uses the repeated expansion of polymer carbon nanotube materials, uses the interaction between electrons and phonons as well as the interaction between phonons and phonons to test the thermal conductivity value and the curing regime of different composite materials at different stages, and in order to study the thermal conductivity of carbon nanotube composites, the relevant data in the model are set to a unified packing density system and melting point, uses the temperature of 280 K and 320 K to normalize the composite materials, and explores the change law of the heat flow correlation function and the thermal conductivity. It can be seen from the experimental data that the heat flow correlation function changes with time and gradually becomes stable and finally fluctuates around 0, which means that the model is in a stable state and the scheme is feasible. With the development of the times, fiber art has various forms of expression, and this art is expected to shine in all walks of life.